Participatory action research to identify a package of interventions to promote postpartum family planning in Burkina Faso and the Democratic Republic of Congo - Nguyen Toan Tran; Wambi Maurice E. Yameogo; Félicité Langwana; Mary Eluned Gaffield; Armando Seuc; Asa Cuzin-Kihl; Seni Kouanda; Désiré Mashinda; Blandine Thieba; Rachel Yodi; Jean Nyandwe Kyloka; Tieba Millogo; et al. (BMC, 2018)
Abstract Background The YAM DAABO study ("your choice" in Mooré) takes place in Burkina Faso and the Democratic Republic of Congo. It has the objective to identify a package of postpartum family planning (PPFP) interventions to strengthen primary healthcare services and determine its effectiveness on contraceptive uptake during the first year postpartum. This article presents the process of identifying the PPFP interventions and its detailed contents. Methods Based on participatory action research principles, we adopted an inclusive process with two complementary approaches: a bottom-up formative approach and a circular reflective approach, both of which involved a wide range of stakeholders. For the bottom-up component, we worked in each country in three formative sites and used qualitative methods to identify barriers and catalysts to PPFP uptake. The results informed the package design which occurred during the circular reflective approach - a research workshop gathering service providers, members of both country research teams, and the WHO coordination team. Results As barriers and catalysts were found to be similar in both countries and with the view to scaling up our strategy to other comparable settings, we identified a common package of six low-cost, low-technology, and easily-scalable interventions that addressed the main service delivery obstacles related to PPFP: (1) refresher training of service providers, (2) regularly scheduled and strengthened supportive supervision of service providers, (3) enhanced availability of services 7 days a week, (4) a counseling tool, (5) appointment cards for women, and (6) invitation letters for partners. Conclusions Our research strategy assumes that postpartum contraceptive uptake can be increased by supporting providers, enhancing the availability of services, and engaging women and their partners. The package does not promote any modern contraceptive method over another but prioritizes the importance of women's right to information and choice regarding postpartum fertility options. The effectiveness of the package will be studied in the experimental phase. If found to be effective, this intervention package may be relevant to and scalable in other parts of Burkina Faso and the DRC, and possibly other Sub-Saharan countries. Trial registration Retrospectively registered in the Pan African Clinical Trials Registry (PACTR201609001784334, 27 September 2016).